2017
DOI: 10.1016/j.bbi.2017.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 signaling in the basolateral amygdala is necessary for heroin-conditioned immunosuppression

Abstract: Heroin administration suppresses the production of inducible nitric oxide (NO), as indicated by changes in splenic inducible nitric oxide synthase (iNOS) and plasma nitrate/nitrite. Since NO is a measure of host defense against infection and disease, this provides evidence that heroin can increase susceptibility to pathogens by directly interacting with the immune system. Previous research in our laboratory has demonstrated that these immunosuppressive effects of heroin can also be conditioned to environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 68 publications
(95 reference statements)
1
12
0
Order By: Relevance
“…In line with our data, it is shown that CBD could downregulate the expression of chemokines (CCL2 and CCL5) and the pro‐inflammatory cytokine IL‐1β, by reduction of the activation of microglia in the PFC in a viral model of multiple sclerosis, through the activation of adenosine A 2A receptors . The role of inflammatory cytokines, 5‐HT 1A , A 2A , and TRPV receptors in the reward system has been established in several studies, which all can be targeted by CBD in order to reduce inflammation . Therefore, we can propose that the reduction in inflammatory cytokines may play an important role in inhibitory effect of CBD on reinstatement of METH seeking.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In line with our data, it is shown that CBD could downregulate the expression of chemokines (CCL2 and CCL5) and the pro‐inflammatory cytokine IL‐1β, by reduction of the activation of microglia in the PFC in a viral model of multiple sclerosis, through the activation of adenosine A 2A receptors . The role of inflammatory cytokines, 5‐HT 1A , A 2A , and TRPV receptors in the reward system has been established in several studies, which all can be targeted by CBD in order to reduce inflammation . Therefore, we can propose that the reduction in inflammatory cytokines may play an important role in inhibitory effect of CBD on reinstatement of METH seeking.…”
Section: Discussionsupporting
confidence: 85%
“…Recent research studies have attempted to clarify the molecular aspects of the neural mechanisms underlying the behavioral effects of drug abuse in different parts of the reward circuitry. Although it is documented that inflammatory factors play roles in reward properties of drugs, there is no report on the possible changes of inflammatory factors in the PFC and hippocampus following the reinstatement of METH‐seeking behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding specialized cell-type-specific IL-1R1 functions could lead to the separation of pathogenic IL-1 activities from its physiological counterparts and isolation of the neurotoxic signaling pathways from neuroprotective ones. Thus far, endothelial cells , astrocytes (Moynagh, 2005), neurons (Hutson et al, 2017), resident microglia (Basu et al, 2004), and perivascular macrophages (Serrats et al, 2010) have been reported to respond to central IL-1. However, in vivo visualization of IL-1R1 in these cells remains challenging because of its low expression.…”
Section: Introductionmentioning
confidence: 99%
“…19 Studies have reported heroin-induced conditioned immunosuppression, which has been shown to depend on central cytokine signaling. 20,21 Data from our laboratory have also suggested an ethanol-induced, conditioned neuroimmune response. Specifically, rats received four pairings of a lemon odor CS with an ethanol (2.0 g/kg, intraperitoneal [i.p.])…”
Section: Impact Statementmentioning
confidence: 95%